Nanomedications in the treatment of melanoma - a review - Pase Ferrari, Débora; Galina Bolzan, Alexandre; Antunes Porciuncula, Joseana; da Silva Araujo Martins, Daniela; Cielo Rech, Virginia; Fernandes, Liana da Silva (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Cutaneous melanoma is a type of cancer that arises from melanocytes, cells responsible for melanin production, formed during embryonic development from the neural crest. This cancer originates in the skin and can be superficial, extensive, nodular, malignant, and acral lentiginous. In this article, we present a literature review on nanomedicines as a possible treatment for this type of cancer. Our search for articles took place on the Web of Science platform over the last 5 years. It was possible to verify that advances in nanoscience led to more modern and effective treatments, with fewer side effects and adverse effects, allowing more safety and quality of life for the patient undergoing treatment.